Implementation of Group Counseling Assisted by Simulation Games at the MGBK SMP in Banyuwangi - Ramli, M; Hidayah, Nur; Rahman, Diniy Hidayatur; Saputra, Nur Mega Aris (Community Development Journal, 2024)
Abstract The implementation of this community service activity is to improve the competence of group counseling services assisted by simulation games at MGBK SMP in Banyuwangi. The implementation of this community service, the structured learning approach (SLA) is intended to improve understanding and application of expected competencies. The activities start from (1) the preparation stage, namely the procedure for preparing the activities to be carried out, (2) the implementation stage for the implementation of group counseling skills training activities with the help of simulation games, (3) Evaluation and Follow Up which is carried out comprehensively including guidelines for observing the implementation of community service, interview guidelines, and questionnaire instruments for group counseling skills competency assisted by simulation games. As for the results of the post-test for improving group counseling skills competency assisted by simulation games, it shows that there has been rapid progress for the participants of the activity, as shown by the results of more than 50% of participants being at level 8 and above or very good achievement. Keywords:Group counseling; simulation games; BK teacher; junior high school; training Abstrak Pelaksanaan kegiatan pengabdian ini adalan untuk meningkatkan kompetensi pelayanan konseling kelompok berbantuan permainan simulasi pada MGBK SMP di Banyuwangi. Pelaksanaan pengabdian ini, pendekatan pembelajaran terstruktur (SLA) juga dikenal sebagai pendekatan pembelajaran terstruktur dimaksudkan untuk meningkatkan pemahaman, contoh, dan penerapan kompetensi yang diharapkan. Adapun kegiatan dimulai dari (1) tahap persiapan yaitu prosedur untuk mempersiapkan kegiatan yang akan dilakukan, (2) Tahap Pelaksanaan untuk kegiatan pelaksanaan pelatihan keterampilan konseling kelompok dengan bantuan permainan simulasi, (3) Evaluasi Dan Follow Up yang dilaksanakan secara menyeluruh meliputi pedoman observasi pelaksanaan pengabdian, pedoman wawancara, dan instrumen kuesioner kompetensi keterampilan konseling kelompok berbantuan permainan simulasi. Adapun untuk hasil post-test peningkatkan kompetensi keterampilan konseling kelompok berbantuan permainan simulasi menunjukkan bahwa ada kemajuan yang pesat bagi peserta kegiatan ditunjukkan dengan hasil 50% lebih peserta berada di angkat 8 keatas atau cakupan sangat baik. Kata kunci: Group counseling; simulation games; BK teacher; junior high school; training